An Introduction to the Process of Making the Indonesian Handmade Batik Lasem - Handhayani, Teny (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Batik is an Indonesian culture that is appointed as an intangible culture by UNESCO in 2009. Batik in Indonesia is categorized as handmade and stamped according to the production process. Indonesian batik has different patterns and motifs depending on their origin. Batik Lasem is a handmade batik from Lasem of Central Java, Indonesia. Batik Lasem has unique charms and mostly bright colors because it is formed from the acculturation of Javanese and Chines. Batik Lasem is mostly produced in Lasem and it is sold in offline and online shops. This is a report on a project on community services from a collaboration between the author and one of the batik shops in Lasem. The project is creating a tutorial to introduce the making of handmade batik. The main tool and ingredients needed for making handmade batik are fabric, canting, wax, and coloring matter. The tutorial contains an explanation of equipment, material, and step by step on making handmade batik. The output of this project is a video and module for learning the basic of making handmade batik.